Measurement of linearity in THz-TDS - Withayachumnankul, Withawat; Ung, Benjamin S.Y.; Fischer, Bernd M.; Abbott, Derek (My University, 2009)
This article presents an approach to the measurement of the amplitude linearity in terahertz time-domain spectroscopy (THz-TDS) systems. The approach exploits a single wafer of high-purity float-zone silicon to produce multiple Fabry-Pérot reflections, which are stepwise attenuated and delayed. Comparison between the theoretical and experimental results can indicate a deviation in linearity. © 2009 IEEE.